Cultivating a Healthy Second Nature - Nature, Culture, and Morality in Danish Parents’ Narratives about their Children’s Overweight and Weight Loss - Andreassen, Pernille; Grøn, Lone; Roessler, Kirsten Kaya (Tidsskrift for Forskning i Sygdom og Samfund, 2013)
Professional explanations for the causes of childhood overweight vary greatly and no particular weight loss methods have proved successful. Nevertheless, parents are generally regarded as primarily to blame for overweight children and also perceived as key to successful weight loss. Based on semi-structured interviews with twelve mothers and two fathers of overweight preschool children, we use a narrative approach to focus on parents’ own aetiological explanations as well as their hopes for a resolution. In their stories of how their children became overweight, parents draw on a number of explanations that refer to both natural and cultural causes which to a large extent mirror the available professional explanations, and in their stories of future possibilities, parents hope to develop a healthy second nature in their children. We argue that the parents employ these hopes and explanations as narrative devices to position themselves as moral actors in relation to the prevalent and widespread idea of childhood overweight as caused by parental failure. The parents’ narratives offer valuable insight into the exceptionally morally charged position of parenting within the social and cultural context of childhood overweight and weight loss.